The need for unbiased genetic screens to dissect aggression in Drosophila melanogaster - Huang, Gary; Dierick, Herman A. (Frontiers in Behavioral Neuroscience, 2022)
Aggression is an evolutionarily conserved behavior present in most animals and is necessary for survival when competing for limited resources and mating partners. Studies have shown that aggression is modulated both genetically and epigenetically, but details of how the molecular and cellular mechanisms interact to determine aggressive behavior remain to be elucidated. In recent decades, Drosophila melanogaster has emerged as a powerful model system to understand the mechanisms that regulate aggression. Surprisingly most of the findings discovered to date have not come from genetic screens despite the fly’s long and successful history of using screens to unravel its biology. Here, we highlight the tools and techniques used to successfully screen for aggression-linked behavioral elements in Drosophila and discuss the potential impact future screens have in advancing our knowledge of the underlying genetic and neural circuits governing aggression.